The effects of recycling on recycled paper properties / Siti Mariam Ismail - Ismail, Siti Mariam (2004)
This review was done to identify the effects of recycling on recycled paper properties. It was based on the quality of the recycled paper to be compared with the quality of paper from virgin pulp. Commonly, tensile, tear and burst properties of paper will decreased after five or six times recycling because of hornification process. After paper drying process, hydrogen bonding already perfect. Some hydrogen bonding can't be break although after soaked in water. The flexibility and fiber swelling of paper will decreased because of the bonding also decreased (Shafie, 2003)